2011
DOI: 10.1002/anie.201103782
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance and Stability of a Polymer Solar Cell by Incorporation of Vertically Aligned, Cross‐Linked Fullerene Nanorods

Abstract: Let the sun shine in: Highly efficient and stable polymer bulk‐heterojunction solar cells can be achieved by the incorporation of vertically oriented, cross‐linked polymer nanorods (see picture). The device exhibits a record power conversion efficiency of 7.3 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(49 citation statements)
references
References 32 publications
1
47
0
1
Order By: Relevance
“…Yoshino et al reported photoconductivity enhancement when polythiophene is blended with C 60 buckyball [100]. After modifying the morphology and device architecture by numerous research group, efficiencies of BHJSCs based on P3HT can now go up to 7 % with external quantum efficiency of around 70 % [101][102][103][104][105]. To address the main issue of large bandgap (>1.9 eV) with P3HT and high HOMO level, which lead to insufficient NIR photon absorption and low V oc of BHJSCs, numerous new organic polymers have been designed for photovoltaic applications.…”
Section: Yd2-o-c8mentioning
confidence: 99%
“…Yoshino et al reported photoconductivity enhancement when polythiophene is blended with C 60 buckyball [100]. After modifying the morphology and device architecture by numerous research group, efficiencies of BHJSCs based on P3HT can now go up to 7 % with external quantum efficiency of around 70 % [101][102][103][104][105]. To address the main issue of large bandgap (>1.9 eV) with P3HT and high HOMO level, which lead to insufficient NIR photon absorption and low V oc of BHJSCs, numerous new organic polymers have been designed for photovoltaic applications.…”
Section: Yd2-o-c8mentioning
confidence: 99%
“…The growing interest in this sector is believed to be fuelled through the ease of fabrication and cost-effective features involved. Such features additionally ensure the potential to obtain highly flexible and light weight devices at a large scale, to realize highly-efficient multifunctional optoelectronic applications [5][6][7][8]. The significance of such hybrid materials actually lies with the usage of inorganic semiconducting nanocrystals, where their higher electron mobility and enhanced optical absorption (on par with the organic acceptors) appears to be the real boosting element [7].…”
Section: Introductionmentioning
confidence: 99%
“…The most exploited donor polymers is regioregular poly(3-hexylthiophene) (P3HT), while the acceptor materials are generally the fullerene derivatives such as [6,6]phenyl C 61 butyric acid methyl ester (PCBM). A bulk heterojunction photovoltaic device combining regioregular P3HT as the electron donor with functionalized fullerenes as the electron acceptor has demonstrated power conversion efficiencies (PCEs) up to 7% [5,6].…”
Section: Introductionmentioning
confidence: 99%